2021
DOI: 10.1093/nutrit/nuab029
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dietary mercury intake during pregnancy on the health of neonates and children: a systematic review

Abstract: Context Growing evidence suggests that prenatal exposure to methyl mercury through the maternal diet could have great influence on the neurological and physical development of neonates and young children. Objective The aim of this review was to evaluate the clinical repercussions of maternal exposure to methyl mercury during pregnancy on the health of fetuses, neonates, and children up to 8 years of age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 45 publications
0
7
1
Order By: Relevance
“…Our findings do not replicate those of a systematic review of maternal dietary mercury intake which included 15 studies of neurodevelopmental outcomes in children up to 8 years old [ 87 ]. The review concluded there was clear evidence that maternal dietary exposure adversely affected childhood cognitive development, although this may be mitigated by nutrients in mercury-containing foods such as fish.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings do not replicate those of a systematic review of maternal dietary mercury intake which included 15 studies of neurodevelopmental outcomes in children up to 8 years old [ 87 ]. The review concluded there was clear evidence that maternal dietary exposure adversely affected childhood cognitive development, although this may be mitigated by nutrients in mercury-containing foods such as fish.…”
Section: Discussioncontrasting
confidence: 99%
“…Hg is a known endocrine disruptor that is able to lower progesterone levels, increase estrogen, and adversely affect the steroid synthesis pathway [ 107 ]. Prenatal exposure to Hg was consistently associated with lower BW [ 110 ].…”
Section: The Most Common Edcsmentioning
confidence: 99%
“…The data are evidence of a clear negative effect of maternal MeHg exposure on anthropometric variables, cognitive or physical growth in children. Furthermore, mercury poisoning might sometimes be lessened by vital nutrients present in the maternal diet ( 66 ). A recent report indicated that moderate fish consumption, consistent with current health recommendations during pregnancy, was related to improvement in the metabolic health of offspring, while higher maternal mercury exposure was related with an unfavorable metabolic profile in children ( 67 ).…”
Section: Impact Of Mercury Exposure On Pregnancy and Outcomementioning
confidence: 99%